BNT162b2 vaccine-induced humoral and cellular responses against SARS-CoV-2 variants in systemic lupus erythematosus. Issue 4 (4th October 2021) - Moyon, Quentin; Sterlin, Delphine; Miyara, Makoto; Anna, François; Mathian, Alexis; Lhote, Raphael; Ghillani-Dalbin, Pascale; Breillat, Paul; Mudumba, Sasi; de Alba, Sophia; Cohen-aubart, Fleur; Haroche, Julien; et al.
Abstract : Objectives: Our aim was to evaluate systemic lupus erythematosus (SLE) disease activity and SARS-CoV-2-specific immune responses after BNT162b2 vaccination. Methods: In this prospective study, disease activity and clinical assessments were recorded from the first dose of vaccine until day 15 after the second dose in 126 patients with SLE. SARS-CoV-2 antibody responses were measured against wild-type spike antigen, while serum-neutralising activity was assessed against the SARS-CoV-2 historical strain and variants of concerns (VOCs). Vaccine-specific T cell responses were quantified by interferon-γ release assay after the second dose. Results: BNT162b2 was well tolerated and no statistically significant variations of BILAG (British Isles Lupus Assessment Group) and SLEDAI (SLE Disease Activity Index) scores were observed throughout the study in patients with SLE with active and inactive disease at baseline. Mycophenolate mofetil (MMF) and methotrexate (MTX) treatments were associated with drastically reduced BNT162b2 antibody response (β=−78, p=0.007; β=−122, p<0.001, respectively). Anti-spike antibody response was positively associated with baseline total immunoglobulin G serum levels, naïve B cell frequencies (β=2, p=0.018; β=2.5, p=0.003) and SARS-CoV-2-specific T cell response (r=0.462, p=0.003). In responders, serum neutralisation activity decreased against VOCs bearing the E484K mutation but remained detectable in a majority of patients. Conclusion: MMF, MTX and poor baseline humoral immune status, particularly low naïve B cell frequencies, are independently associated with impaired BNT162b2 mRNA antibody response, delineating patients with SLE who might need adapted vaccine regimens and follow-up.